2013
DOI: 10.4140/tcp.n.2013.775
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pharmacy-Driven Inpatient Discharge Counseling Service: Impact on 30-Day Readmission Rates

Abstract: Pharmacy discharge counseling was associated with reduced 30-day readmission rates in those patients at moderate risk for readmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 8 publications
0
33
1
Order By: Relevance
“…The beneficial effects of patient discharge counselling on patient outcomes include decreased adverse drug events and 30 day readmission rates. 4,66,67 Amy, relayed an incident of helping a patient understand the rationale for their medication and the patient's appreciation of this knowledge.…”
Section: Improving Patients' Experiences Health and Safetymentioning
confidence: 99%
“…The beneficial effects of patient discharge counselling on patient outcomes include decreased adverse drug events and 30 day readmission rates. 4,66,67 Amy, relayed an incident of helping a patient understand the rationale for their medication and the patient's appreciation of this knowledge.…”
Section: Improving Patients' Experiences Health and Safetymentioning
confidence: 99%
“…Given these parameters, patient participation in the PPMDP did not reduce hospital 30-day readmission rate. Previous studies have shown varying reports of pharmacist intervention and reducing readmission rates; [5][6][7] however, these studies did not look at pediatric patients. Rate of readmission in this study was higher at 12.7% compared to a previously reported rate of 6.5% for pediatric patients.…”
Section: Discussionmentioning
confidence: 94%
“…5 Pharmacistdriven discharge counseling was associated with decreased 30-day readmission rates for adult internal medication moderate-risk patients and averaged 4 pharmacy interventions per patient. 6 Extrapolating these results to pediatric patients, the investigators hypothesized that participation in the program led to increased medication adherence and understanding of medications, and therefore decreased rates of readmission.…”
Section: Introductionmentioning
confidence: 99%
“…It combined the bedside face‐to‐face counselling and the use of a leaflet, which have been demonstrated to be effective in improving the patients’ knowledge about medications if used concurrently . The counselling intervention enables a two‐way communication between pharmacists and patients, while the leaflet helps the patients to recall the instructions given by pharmacists after discharge from hospitals …”
Section: Discussionmentioning
confidence: 99%